Structure-function relationships in an anion-translocating ATPase. (August 2000) - Bhattacharjee, H.; Zhou, T.; Li, J.; Gatti, D. L.; Walmsley, A. R.; Rosen, B. P.
Abstract : The ArsAB ATPase is an efflux pump located in the inner membrane of Escherichia coli. This transport ATPase confers resistance to arsenite and antimonite by their extrusion from the cells. The pump is composed of two subunits, the catalytic ArsA subunit and the membrane subunit ArsB. The complex is similar in many ways to ATP-binding cassette ('ABC') transporters, which typically have two groups of six transmembrane-spanning helical segments and two nucleotide-binding domains (NBDs). The 45 kDa ArsB protein has 12 transmembrane-spanning segments. ArsB contains the substrate translocation pathway and is capable of functioning as an anion uniporter. The 63 kDa ArsA protein is a substrate-activated ATPase. It has two homologous halves, A1 and A2, which are clearly the result of an ancestral gene duplication and fusion. Each half has a consensus NBD. The mechanism of allosteric activation of the ArsA ATPase has been elucidated by a combination of molecular genetics and biochemical, structural and kinetic analyses. Conformational changes produced by binding of substrates, activator and/or products could be revealed by stopped-flow fluorescence measurements with single-tryptophan derivatives of ArsA. The results demonstrate that the rate-limiting step in the overall reaction is a slow isomerization between two conformations of the enzyme. Allosteric activation increases the rate of this isomerization such that product release becomes rate-limiting, thus accelerating catalysis. ABC transporters, which exhibit similar substrate activation of ATPase activity, can undergo similar conformational changes to overcome a rate-limiting step. Thus the ArsAB pump is a useful model for elucidating mechanistic aspects of the ABC superfamily of transport ATPases.